Encarnación : illness and body politics in Chicana feminist literature - Bost, Suzanne (Fordham University Press, 2010)
'Encarnación' takes a new look at identity. Following the contemporary movement away from the fixed categories of identity politics toward a more fluid conception of the intersections between identities and communities, this book analyzes the ways in which literature and philosophy draw boundaries around identity.